Comparison of Cognitive Behavior Therapy and Islamic Based Spiritual Religion Psychotherapy on the Intensity of the Symptoms of Obsessive- Compulsive of Women with Washing Compulsive - Sepideh Mortezaeifar (Alzahra University, 2021)
The present study was conducted to investigate the comparison of cognitive behavior therapy and Islamic based spiritual religion psychotherapy on the Intensity of the Symptoms of obsessive- compulsive of women with washing compulsive. The research is a semi-experimental one with pretest-posttest design and control group. The research population includes all women with washing compulsive disorder who referred to Tehran city’s Psychiatry and Psychotherapy Centers in 2018. Among them, 39 people selected in the form of purposefully method and then randomly assigned to three groups of 13. Cognitive-behavioral therapy on the first experimental group and Islamic based spiritual religion psychotherapy on the second experimental group, during eight 120-min sessions 1 sessions a week. The third group, i.e., control group was put in the waiting list. In order to collect data, Yale-Brown Obsessive-Compulsive were used. Univariate analysis of variance and Fisher's post hoc test were used for analysis of data. The results showed that both cognitive behavior therapy and Islamic based spiritual religion psychotherapy have been effective in reducing obsessive-compulsive disorder, and there was not obsessed a significant difference between the efficacy of these two therapies in reducing the severity of obsessive- compulsive of women with washing compulsive